2012
DOI: 10.1128/jvi.00688-11
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Ras/Raf/MEK Pathway Facilitates Hepatitis C Virus Replication via Attenuation of the Interferon-JAK-STAT Pathway

Abstract: Hepatitis C virus (HCV) is a major cause of chronic liver diseases worldwide, often leading to the development of hepatocellular carcinoma (HCC). Constitutive activation of the Ras/Raf/MEK pathway is responsible for approximately 30% of cancers. Here we attempted to address the correlation between activation of this pathway and HCV replication. We showed that knockdown of Raf1 inhibits HCV replication, while activation of the Ras/Raf/MEK pathway by V12, a constitutively active form of Ras, stimulates HCV repli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 75 publications
5
53
1
Order By: Relevance
“…Several studies have indicated that these factors, including those encoding OAS and PKR, could inhibit HCV infection (32,43,44,63,64). In the present study, we showed that overexpression of Set7 inhibited virusinduced IFN-a, IFN-b, PKR, and OAS activation; however, both knockdown of Set7 and inhibition of Set7 enzymatic activity demonstrated reverse effects.…”
Section: Discussionsupporting
confidence: 47%
See 3 more Smart Citations
“…Several studies have indicated that these factors, including those encoding OAS and PKR, could inhibit HCV infection (32,43,44,63,64). In the present study, we showed that overexpression of Set7 inhibited virusinduced IFN-a, IFN-b, PKR, and OAS activation; however, both knockdown of Set7 and inhibition of Set7 enzymatic activity demonstrated reverse effects.…”
Section: Discussionsupporting
confidence: 47%
“…Presently, IFN-a alone or in combination with ribavirin is the most common and effective therapy strategy for HCV (51, (32,53). Our above results showed that the SeVinduced mRNA of both PKR and OAS were inhibited by Set7.…”
Section: Set7 Suppresses the Expression Of Ifn-induced Downstream Effmentioning
confidence: 57%
See 2 more Smart Citations
“…In the ligand-independent pathway, the unfolded-protein response (UPR) activates p38 kinase, which subsequently phosphorylates IFNAR1 at Ser532 (35)(36)(37)(38). We previously reported that extracellular signal-regulated kinase (ERK) is involved in the degradation of IFNAR1 (39,40). Here, the signaling pathways that participated in the MMP-9-mediated degradation of IFNAR1 were evaluated in HepG2 cells transfected with pCMV-Tag2B-MMP-9 and treated with the signaling component inhibitors SB203580 (p38 mitogen-activated protein kinase [MAPK] inhibitor), U0126 (ERK1/2 inhibitor), and PD98059 (MEK inhibitor).…”
Section: Resultsmentioning
confidence: 99%